2011
DOI: 10.1021/jp203743m
|View full text |Cite
|
Sign up to set email alerts
|

FRET-FCS Detection of Intralobe Dynamics in Calmodulin

Abstract: Fluorescence correlation spectroscopy (FCS) can be coupled with Förster resonance energy transfer (FRET) to detect intramolecular dynamics of proteins on the microsecond time scale. Here we describe application of FRET-FCS to detect fluctuations within the N-terminal and C-terminal domains of the Ca2+-signaling protein calmodulin. Intramolecular fluctuations were resolved by global fitting of the two fluorescence autocorrelation functions (green-green and red-red) together with the two cross-correlation functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 59 publications
(131 reference statements)
1
31
0
Order By: Relevance
“…Although T4L hinge-bending motion has long been postulated (15), FCS enables a determination of its timescale in the range of~10-20 ms. Relaxation times in the range of microseconds to hundreds of microseconds have been reported for fluctuations arising from domain motions as well as transitions to partially unfolded states (30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although T4L hinge-bending motion has long been postulated (15), FCS enables a determination of its timescale in the range of~10-20 ms. Relaxation times in the range of microseconds to hundreds of microseconds have been reported for fluctuations arising from domain motions as well as transitions to partially unfolded states (30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in the early seventies (25), FCS has been used to examine a variety of systems including the photophysical behavior of fluorescent proteins (26,27) as well as macromolecular diffusion and interactions (28,29). In addition, FCS has been demonstrated to be a powerful tool for the investigation of equilibrium protein conformational and folding dynamics (30)(31)(32)(33)(34)(35). Hence, this technique is inherently suited to study the type of domain motion observed in T4L with the ultimate goal of obtaining a fluctuation timescale.…”
Section: Introductionmentioning
confidence: 99%
“…For example BiFC has been used in FCS to investigate the recruitment of β-arrestin to NPY Y receptors [15]. FCS techniques have also been combined with FRET to investigate the dynamics of conformational changes of syntaxin-1 [34] and calmodulin [35]. …”
Section: Using Fcs To Provide Insights Into the Molecular Pharmacologmentioning
confidence: 99%
“…FCS measurements can be used to determine the timescale of conformational dynamics that are faster than the diffusion time. [124] Applications of this approach include the characterization of conformational dynamics of calmodulin, [130] diffusing biopolymers, [131] and glutamate receptor transitions. [132] In FRET-FCS, the signal of the donor is cross-correlated with the www.advancedsciencenews.com www.bioessays-journal.com acceptor channel.…”
Section: Fret-fcsmentioning
confidence: 99%